Teaching with Compassion and Mindfulness: Correlating Workplace Spirituality and Professional Competence among Edukasyon sa Pagpapakatao (EsP) Teachers - , Elden D. Orbeta (Archives of Current Research International, 2025)
This study investigated the relationship between workplace spirituality and the professional competence of Edukasyon sa Pagapapakatao (EsP) teachers in the Division of Panabo City. To gather data, researchers utilized the Workplace Spirituality Scale along with three years of Individual Performance Commitment and Review Form (IPCRF) ratings from 2019 to 2022, involving 306 teachers across four districts. The approach taken was quantitative, non-experimental, and descriptive-correlational. The results revealed that teachers exhibited a high level of workplace spirituality, particularly in compassion, meaningful work, transcendence, and mindfulness. Correlation analysis confirmed significant relationships between certain aspects of spirituality and teaching effectiveness. However, regression analysis indicated that workplace spirituality alone didn’t significantly predict professional competence, suggesting that other elements like leadership, ethical conduct, and ongoing professional development could play a more crucial role. Professional competence consistently registered at the Outstanding level. Correlation analysis confirmed significant relationship between select domains of workplace spirituality – especially compassion and mindfulness – and professional competence. However, regression analysis indicated that workplace spirituality alone did not significantly predict competence, suggesting that other determinants such as ethical behavior, leadership, and ongoing professional development may exert stringer influence. The findings underscore the importance of cultivating not only a values-driven work but also sustained professional growth to enhance teaching effectiveness. This study offers actionable insights for education leaders and policymakers. By aligning values formation with competence-building, the the findings support more response, human-centered policies that elevate the quality of EsP instruction and reinforce the broader goals of values education in the Philippine context.